The VIRI (Virtual, Interactive, Real-Time, Instructor-Led) Classroom: The Impact of Blended Synchronous Online Courses on Student Performance, Engagement, and Satisfaction - Francescucci, Anthony; Foster, Mary (Canadian Journal of Higher Education, 2013)
Previous research on blended course offerings focuses on the addition of asynchronous online content to an existing course. While some explore synchronous communication, few control for differences between treatment groups. This study investigates the impact of teaching a blended course, using a virtual, interactive, real-time, instructor-led (VIRI) classroom, on student engagement, performance, and satisfaction. We use an experimental design with both a control group and a treatment group. Up to 90 students in a large urban university are randomly assigned by the registrar into two sections of an introductory marketing course. Using a pre- and post-semester questionnaire, the study measures student engagement, performance, and satisfaction. There are no statistical differences in student performance between the control and treatment groups. The only student engagement factor with a statistically significant difference between groups is student interest in their courses. Compared with the control group, the treatment group appears to be more interested (+10%) in their courses at the end of the semester. Finally, fewer than 2 in 10 students express dissatisfaction with their participation in a VIRI course. Blended course offerings are increasing in importance in marketing and business education. The study provides guidance for fine-tuning the features of those course offerings by demonstrating how a VIRI classroom leverages the capabilities of technology without compromising learning outcomes.